2021
DOI: 10.1021/acsaelm.0c00933
|View full text |Cite
|
Sign up to set email alerts
|

B-Site Stoichiometry Control of the Magnetotransport Properties of Epitaxial Sr2FeMoO6 Thin Film

Abstract: The high degree of spin-polarization observed in ordered double perovskite oxide Sr 2 FeMoO 6 at room temperature has attracted considerable interest from both fundamental and practical points of view. In this paper, we have shown a significant change in spin-polarization with a small B-site offstoichiometry. We have demonstrated a direct correlation between the growth process, Fe:Mo (B-site) stoichiometry, and the electrical properties of half metallic Sr 2 FeMoO 6 thin film. We have shown that varying the Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Isothermal M – H hysteresis loops at 5 and 300 K shown in the inset of Figure are typical of a soft ferromagnet with a rapid increase at low fields and a tendency to saturate at H = 70 kOe and 5 K. At 5 K, the coercivity is 153.6 Oe and saturation magnetization is M S = 3.3 μ B /fu at 70 kOe. The obtained M S value is closer to the saturation magnetization of 4 μ B /fu expected based on the coupling between the perfectly ordered Fe 3+ and Mo 5+ ions, via Fe­( t 2g )–O­(2p)–Mo­( t 2g ) hybridization, at the B and B′ sites, respectively. ,, However, an antisite disorder (B = Fe 3+ ions at B′= Mo sites in the lattice or vice versa) and antiphase domain boundaries that separate two antisite domains of the same ordered phase can lower the saturation magnetization. …”
Section: Resultssupporting
confidence: 61%
“…Isothermal M – H hysteresis loops at 5 and 300 K shown in the inset of Figure are typical of a soft ferromagnet with a rapid increase at low fields and a tendency to saturate at H = 70 kOe and 5 K. At 5 K, the coercivity is 153.6 Oe and saturation magnetization is M S = 3.3 μ B /fu at 70 kOe. The obtained M S value is closer to the saturation magnetization of 4 μ B /fu expected based on the coupling between the perfectly ordered Fe 3+ and Mo 5+ ions, via Fe­( t 2g )–O­(2p)–Mo­( t 2g ) hybridization, at the B and B′ sites, respectively. ,, However, an antisite disorder (B = Fe 3+ ions at B′= Mo sites in the lattice or vice versa) and antiphase domain boundaries that separate two antisite domains of the same ordered phase can lower the saturation magnetization. …”
Section: Resultssupporting
confidence: 61%
“…For example, Kumar et al grew epitaxial SFMO thin films on SrTiO 3 (STO) (001) substrates by the PLD method. 161 They found that the laser fluence has a strong influence on the microstructural and physical properties of the SFMO thin films. Fig.…”
Section: Pulsed Laser Deposition (Pld)mentioning
confidence: 99%
“…The EDAX results have error bars of AE1%. Reproduced with permission 161. Copyright 2021, American Chemical Society.…”
mentioning
confidence: 99%
“…Physical properties, especially magnetism in DPs, can be highly influenced by appropriate growth conditions in thin films. In particular strain, oxygen stoichiometry, fluence, and growth temperature control the structure, magnetism, and transport properties [15,18,19]. Most of the DP thin films are grown using pulsed laser deposition (PLD).…”
Section: Introductionmentioning
confidence: 99%